2014
DOI: 10.1016/j.talanta.2014.07.013
|View full text |Cite
|
Sign up to set email alerts
|

Immobilization of His-tagged kinase JAK2 onto the surface of a plasmon resonance gold disc modified with different copper (II) complexes

Abstract: New surface plasmon resonance (SPR) sensing platform swhich consists of copper (II) complexes of a pentetic acid thiol ligand (DPTA-Cu(II)) and of a thiol derivative of dipyrromethene (DPM-Cu(II) created on the surface of gold SPR disc were applied to oriented immobilization of His-tagged Janus kinase 2 (GST-His 6 -JAK2). This method is based on the covalent bond formation between histidine from a His-tag chain of a protein and Cu(II) centres from the complexes. The kinetic and thermodynamic parameters of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…Additionally, surface plasmon resonance (SPR) technology can monitor the interaction between molecules in real-time and offer a label-free detection, which is also considered in screening PAs [163]. Canabady-Rochelle et al developed an SPR strategy for screening metal-chelating peptides in hydrolysates, which can detect the presence of metal-chelating peptides in hydrolysate faster before starting the separation stage, and has great potential for industrial application [164].…”
Section: Purification Of Pasmentioning
confidence: 99%
“…Additionally, surface plasmon resonance (SPR) technology can monitor the interaction between molecules in real-time and offer a label-free detection, which is also considered in screening PAs [163]. Canabady-Rochelle et al developed an SPR strategy for screening metal-chelating peptides in hydrolysates, which can detect the presence of metal-chelating peptides in hydrolysate faster before starting the separation stage, and has great potential for industrial application [164].…”
Section: Purification Of Pasmentioning
confidence: 99%
“…By reference with other works reported in the literature, the reason of this success can probably be associated with the presence of an hexahistidine tag (his‐tag) added at the C ‐terminal extremity of the enzyme . Kurzatkowska et al have already reported the exploitation of his‐tag to ensure an enzyme immobilization in a proper orientation, or at least, to initiate an attachment which could then be supplemented by other interactions with the rest of the enzyme structure, and consequently, preventing or limiting the interaction and/or masking of the enzyme active site. Martin et al have also reported that his‐tagged biomolecules can be covalently immobilized on supports through the nucleophilic reaction of the imidazole group (i.e., secondary amine) with the epoxy groups.…”
Section: Resultsmentioning
confidence: 97%
“…The easiest way to immobilize proteins is to limit the modifications within the region not involved in the interactions of antigen. Immobilized metal ion affinity chromatography (IMAC) mediated by a fused poly-histidine tag (His-tag) has been used as a simple and inexpensive purification technique for the high-throughput production of proteins in industry [15,16,17]. IMAC has also been extended to various other applications, such as the immobilization of proteins on chips and nanomaterials [18,19,20], and the incorporation of labeled molecules to active proteins [21,22,23,24].…”
Section: Introductionmentioning
confidence: 99%